Optimizing Supply Chain Resilience through Robust Production Planning - Zhank Loh Blackhurst (International Journal of Enterprise Modelling, 2021)
This study focuses on improving supply chain resilience through careful production planning. The study helps to the understanding of how firms can increase their ability to endure disruptions and improve overall supply chain performance by generating a mathematical framework and offering a numerical example. The study emphasizes the need of factoring in aspects such as demand uncertainty, manufacturing capacity, inventory management, and supply chain disruption costs when making decisions. The proposed mathematical concept enables firms to reduce costs, satisfy demand, effectively allocate resources, and improve supply chain resilience. It is critical to recognize the research's limitations. When applying the findings to real-world supply chain contexts, the simplified assumptions, limited generalizability, data availability and quality concerns, computational complexity, subjective trade-offs, and lack of validation must all be considered. Future research should concentrate on overcoming these constraints and improving the model to account for the intricacies and dynamism of various supply chain situations. Empirical validation and case studies using real-world data would provide further insights and improve the research findings' applicability. This study adds to the body of knowledge in supply chain management and optimization by presenting a paradigm for robust production planning that takes supply chain resilience into account. Businesses can increase their ability to respond, manage risks, and preserve operational continuity in the event of interruptions by optimizing production quantities, inventory levels, and supply allocation. In today's increasingly turbulent business climate, achieving a robust supply chain improves customer happiness, lowers costs, and improves overall business performance.